Towards a new equality narrative. (August 2021) - Crilly, Elizabeth; Voice, Alison; Pugh, Samantha
Abstract : Valuing and recognizing other sources of technical knowledge – rather than just pure scientific competence – can help to encourage more people from under-represented groups into physics